The impact of capital structure on abnormal return: does family control impact? - Lisboa, Inês (2017)
Purpose: This study analyses the impact of family control in the relationship between abnormal returns and gearing for Portuguese listed firms. Moreover, it provides new evidence on this field taking into account firms’ heterogeneities, namely size effect. Design/methodology/approach: This paper uses a panel data of Portuguese listed firms with different capital structure and various industries. The sample period is from 1999 to 2012. Findings: The models results show that size effect causes inference on results. To small-size firms, abnormal return declines with firm’s gearing, but it increases with market gearing to large-size firms. To the overall sample firm’s gearing in insignificant in explaining the firm’s abnormal return. Moreover, firm’s performance and risk, and free-risk rate cause impact on abnormal return. Practical implications: The paper conclusions are relevant for institutional and individual investors, since they have more information about Portuguese firms and about the impact of gearing on the firm’s abnormal return. Results are also important for practitioners, because it expands international evidence on abnormal return, which are focused on large countries as the U.K. and the U.S. Originality/value: The majority of the studies in this research area focus on the impact of gearing on abnormal returns. This study goes a step further introducing the impact of family control on this relationship. Moreover, I also take into account the firm’s heterogeneities, offering new insights to this stream.